When the Cloud Runs out of its Silver Lining - Ravindran, Kiron; Gonzalez Muñoz, Juan Manuel; van den Bergh, Alex (Routledge, 2020)
Cloud computing services are central to most organizations’ IT portfolio. Adopting a cloud computing strategy typically involves a one-way migration of IT skills and capabilities out of the organization. Therefore, it is interesting to observe what happens when organizations wish to end such engagements. Based on a survey of Spanish firms, we list some key insights on software as a service (SaaS) contracts in comparison to contracts containing Application development and maintenance and others containing hardware services. We find that satisfaction levels are generally high and premature termination is lower in the case of SaaS contracts compared to application development and hardware contracts. Post-termination, the typical strategy is to move to new external providers. Termination is associated with vendors’ service quality rather than relationship management. Unlike in the case of application or hardware contracts, SaaS contracts do not appear to suffer from the challenges of know-how transfer.
Keywords: Outsourcing; SaaS; Termination; Exit Satisfaction; 53 Ciencias Económicas; ODS 9 - Industria, innovación e infraestructura